Value-Based Rationality And Normative Rationality Of Management In Russia - Nigomatullina, Rezida M. (2019)
In this work, they attempted to deconstruct the syncretic concept that was set in Russian social science — normative-value consciousness. Basic concepts - norms and values, are included in another context of analysis - the idea of social activity rationality, including management. The necessity of distinguishing between value and normative rationalities is substantiated to understand the mechanisms of building different types of communications in management. They showed that value rationality is formed as the way of consciousness individualization, simultaneously as the way of building the universal in culture, however, its absolutization creates the condition for building an authoritarian, vertical hierarchy both in the internal spiritual life, and in the external social, ideological, and administrative. Ideological regulators ultimately form double moral standards that minimize the effects of social modernization. Normative rationality mediates the contractual relationships that underlie democratic, horizontal communications in governance. The following concepts are relevant: instrumental rationality, purposeful activity, institutional reality. However, the substitution of one for the other in both cases leads to the irrationalization of management processes.